Stock Market Development and Economic Growth: Evidences from Asia-4 Countries - Azam, Muhammad; Haseeb, Muhammad; Samsi, Aznita binti; Raji, Jimoh Olajide (International Journal of Economics and Financial Issues, 2016)
The main purpose of this study is to examine the role of stock markets in economic growth for four Asian countries namely Bangladesh, India, China and Singapore. Annual time series cross country data over the period 1991 to 2012 and Autoregressive Distributed Lag (ARDL) bound testing approaches an analytical technique are used. Our results suggest that there is long-term cointegration among economic growth, Foreign Direct Investment (FDI), stock market development and inflation. The long-term elasticity estimates of the stock market development in all countries show expected sign but statistically significant only in China and Singapore. Incoming FDI is found to have positive relation to economic growth in all countries except India and statistically insignificant for all countries except China. In the short run, stock market also has positive relation to economic growth in all countries but significant only in India and China. The impact of FDI on growth is significant and positive only for Singapore. The results indicate that the inflation variable is statistically significant in Bangladesh and Singapore. The empirical findings of the study reveal that stock market development and FDI inflows play vital roles in the process of economic growth and development in these selected countries. Keywords: Economic growth, stock market, ARDL model, Asia-4 countries JEL Classifications: C22, O16, O40, O53